P05.84 Clinical and radiological patterns of brain radiation necrosis after ion beam radiotherapy for head and neck tumors. (19th September 2018) - Picca, A; Berzero, G; Diamanti, L; Bini, P; Bacila, A; Farina, L; Bernini, S; D'Ippolito, E; Preda, L; Iannalfi, A
Abstract: Background: beam radiotherapy (IBRT) is increasingly used for the treatment of head/neck cancers in order to spare radiosensitive structures. The occurrence of brain radiation necrosis (RN) following this modality has been reported in small case series, although its long-term outcome has not been clarified yet. The aim of this study is to define the clinical and radiological course of brain RN after IBRT, with a focus on neuropsychological (NPS) deficits and epilepsy. Material and Methods: Patients were prospectively identified from 07/2014 to 10/2017 during their follow-up at CNAO Foundation. Inclusion criteria were: 1) history of IBRT for a head/neck cancer; 2) age ≥18 years at the time of IBRT; 3) new MRI alterations compatible with brain RN. Enrolled patients underwent multimodal evaluations (including neurological examination, contrast brain MRI, EEG, and NPS testing), at the time of RN detection, after three months and then every six months. Results: A total of 22 patients were identified. All of them had received IBRT for intracranial extraparenchymal tumors. Median age at the time of IBRT was 49 years (range 29–64). IBRT consisted of protons in 9 cases and of carbon ions in 13 cases. Median total dose was 68.8 Gy[RBE] (range 14–76.8). Six patients had been previously irradiated. Median time from the end of IBRT to RN identification was 16 months (range 3–37). In 86% of cases, RN was identified during scheduled MRI scans. RN was located in the temporal lobes in 21 cases (95%). At the time of RN detection, 71% of the patients tested had NPS deficits. Six patients developed seizures (27%). Patients were followed for a median of 23 months (range 4–41). Sixteen patients (73%) needed corticosteroid therapy and 9 (41%) were started on antiepileptic drugs. At last follow-up, 35% of patients still had multidomain NPS deficits. Within the first six months of follow-up, 74% of patients had the appearance of new enhancing lesions o enlargement of previously described lesions on MRI, though in most cases RN was reduced at last radiological follow-up. Conclusion: The incidence of RN peaks during the second year after IBRT. Although in most cases RN was identified during scheduled MRI scans, cognitive deficits and symptomatic epilepsy were detected in a large proportion of patients. Long-term outcome is not predictable, as some patients tend to improve over time, while others develop new symptoms. Corticosteroids and antiepileptic drugs are needed in most patients to control symptoms.